Fluorene-based enamines as low-cost and dopant-free hole transporting materials for high performance and stable perovskite solar cells. Issue 1 (8th December 2020) - Daskeviciute, Sarune; Momblona, Cristina; Rakstys, Kasparas; Sutanto, Albertus Adrian; Daskeviciene, Maryte; Jankauskas, Vygintas; Gruodis, Alytis; Bubniene, Giedre; Getautis, Vytautas; Nazeeruddin, Mohammad Khaja
Abstract : One-pot synthesized low-cost HTM V1275 exhibits a remarkable performance of 19.3% in PSCs with exceptional stability retaining 125% of the original PCE after 500 h. Abstract : The power conversion efficiency of perovskite solar cells is approaching the Shockley–Queisser limit, and therefore this technology is next to the commercialization stage. Inexpensive and stable hole transporting materials are highly desirable for the successful scale-up. Most high performing devices generally employ expensive hole conductors that are synthesized via cross-coupling reactions which require expensive catalysts, inert reaction conditions and time-consuming sophisticated product purification. In a quest to employ cost-effective chemistry to combine the building blocks, we explore enamine-based small molecules that can be synthesized in a simple condensation reaction from commercially available materials leading to an estimated material cost of a few euros per gram. The synthesized fluorene-based enamines exhibit a very high hole mobility up to 3.3 × 10 −4 cm 2 V −1 s −1 and enable the fabrication of perovskite solar cells with a maximum power conversion efficiency of 19.3% in a doped configuration and 17.1% without doping. In addition, both PSC systems demonstrate superior long-term stability compared to spiro-OMeTAD. This work shows that hole transporting materials prepared via a simple condensation protocol have the potential to compete in terms of performance with materials obtained via expensive cross-coupling methods at a fraction of their cost and deliver exceptional stability of the final device. This work provides a design strategy for the further development of novel, low-cost semiconductors.